KEEFEKTIFAN KONSELING KELOMPOK TEKNIK THOUGHT STOPPING UNTUK MENGURANGI KECANDUAN JUDI ONLINE (SLOT) PADA MAHASISWA - Aziz, Beny; Rasmanah, Manah; Utami Fitri, Hartika (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2024)
This research is motivated by the increase in cases of online gambling addiction, especially slots, among students. This addiction hurts students' academic, social, and psychological lives, so effective intervention is needed to overcome it. The purpose of this research is to find out the picture and effectiveness of group counseling with the thought-stopping technique to reduce online gambling addiction in students. The population is 85 students of the BPI study program, the sample taken is 8 people using the purposive sampling technique, which is a method of drawing non-random sampling samples that is carried out with certain criteria. Data collection techniques include using questionnaires or questionnaires and documentation. Data analysis techniques using the Wilcoxon Signed Rank Test measure the significance of the difference between two populations based on samples.The results of this study concluded that the average pretest before M(SD) was 86,714 (3,773) and after the post-test M(SD) was 51,875 (5,194) Experiencing a decrease in online gambling addiction. Wilcoxon test results With Zscore = -2.533 with a significance value of 0.011 The results showed a difference between before and after group counseling with the thought-stopping technique